2015
DOI: 10.1002/jso.23942
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Sparing Surgery for Localized Ovarian Cancers Maintains an Ability to Conceive, but is Associated With Diminished Reproductive Potential

Abstract: FSS maintains an ability to conceive for most patients. However, after FSS, there may be risks of infertility, early menopause with earlier age of treatment, and increased probability of disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…17 In another study of 82 women who had FSS, only 7% had permanent cessation of menses. 97 Few studies have reported the number of women who actually attempted conception following FSS, which is estimated to be lower than expected at 16-50%, making it difficult to estimate pregnancy rates. 68 In the limited number of high-quality studies that do exist, successful pregnancy rates average 60% and miscarriage rates average 15% (Table 3).…”
Section: Reproductive Outcomes Following Fss For Eocmentioning
confidence: 99%
“…17 In another study of 82 women who had FSS, only 7% had permanent cessation of menses. 97 Few studies have reported the number of women who actually attempted conception following FSS, which is estimated to be lower than expected at 16-50%, making it difficult to estimate pregnancy rates. 68 In the limited number of high-quality studies that do exist, successful pregnancy rates average 60% and miscarriage rates average 15% (Table 3).…”
Section: Reproductive Outcomes Following Fss For Eocmentioning
confidence: 99%
“…Thus, quality of life issues, such as the maintenance of fertility, are important and fertility-sparing treatment options are integral to the care of reproductive-aged women with cancer without compromising cancer outcomes[6]. Fertility-sparing surgery for localized gynecological cancers has been associated with a significant number of post-treatment pregnancies[7]. When faced with a diagnosis of cancer, patients face an onslaught of information and are tasked with making many decisions regarding the next steps of their care.…”
Section: Introductionmentioning
confidence: 99%
“…La pre´servation de la fertilite´doit-elle influencer la strate´gie the´rapeutique en cas de cancer de l'ovaire de stade I ? Selon les auteurs, de 1/3 [3], à 2/3 [4] des femmes é ligibles pour une chirurgie pré servant la fertilité souhaiteraient ce type de prise en charge conservatrice (NP3). L'information concernant les possibilité s de pré servation de la fertilité doit être conduite pré alablement au traitement chez les femmes de moins de 40 ans ayant encore un projet de grossesse conformé ment aux recommandations antérieures de l'INCa.…”
Section: Ré Sultatsunclassified
“…En cas d'annexectomie unilaté rale chez la femme adulte dans un contexte de tumeur ovarienne localisé e, le risque d'insuffisance ovarienne pré maturé e (IOP) avec amé norrhé e avant 40 ans est augmenté [4] (NP4). Dans la sé rie ré trospective de 245 femmes de Letourneau et al [4] qui ne comptait que 17 tumeurs é pithé liales de l'ovaire, 7 % des femmes ont rapporté une disparition des cycles menstruels aprè s annexectomie unilaté rale, cette amé norrhé e post-chirurgie touchant surtout les femmes plus âgé es de 36 ans. En revanche, chez les femmes toujours ré glé es aprè s annexectomie unilaté rale, le risque d'IOP semblait surtout toucher les femmes plus jeunes.…”
Section: Quelles Strate´gies Comple´mentaires De Pre´servation De La unclassified
See 1 more Smart Citation